(NgRAF mONTE(B-(NkRISTO(B: [(NrOMAN(B] / s (N~ASTX (B2s - (Nd@MA(B, (NaLEKSANDRs ((NmOSKWA(B: s (NpRAWDA(B, s, 1983)
"(NgRAF mONTE(B-(NkRISTO(B" - (NPOPULQRNYJ ROMAN aLEKSANDRA d@MA(B-(NOTCA(B. (NwO WTOROJ TOM WHODQT POSLEDNIE TRI ^ASTI ROMANA(B.s
rus
Keywords: (NiSTORI^ESKIJ ROMANs